Sustainable Design and Evaluation of Coconut Coir as an Insulation Material for Taho Containers - Ong, Vin Cedric C. (Animo Repository, 2024)
Upcycling is a sustainable approach towards waste; it makes use of used materials and transforms them into new and improved products. This approach can also be applied to coconut coir, a natural fiber in coconut husks, which are usually just waste, as most farmers harvest coconuts only for their flesh and water. With upcycling, the large volume of discarded coconut coir can be converted into an opportunity to develop a sustainable insulator specifically for taho containers. The aluminum containers of taho, while light and strong, which are necessary for carrying the container more easily, are also good conductors of heat. This is a problem for taho vendors as their taho becomes less desirable to consume when it is already cold, causing a loss of potential customers who prefer hot taho. Therefore, this study addresses this problem by developing a sustainable insulation material made up of coconut coir for taho containers. Evaluation was done to determine its insulating properties by monitoring the temperature loss of taho in the container in different conditions. It has been observed through experiments that the taho insulator can retain heat 7°C warmer versus no insulation. It is then proven that coconut coir is a good alternative insulation material.